Managing oneself or managing together? Parents' perspectives on chronic condition self-management in Dutch pediatric rehabilitation services. Issue 23 (5th November 2020) - Wong Chung, Ruud; Willemen, Agnes; Voorman, Jeanine; Ketelaar, Marjolijn; Becher, Jules; Verheijden, Johannes; Schuengel, Carlo
Abstract: Purpose: With the growing attention in pediatric rehabilitation services for supporting self-management, the need increases for more shared understanding of the concept. The aim of this study was to explore parent activation, associated factors of- and underlying perceptions on parental self-management of parents of children with chronic conditions. Materials and methods: Using a mixed-methods strategy, first variations in self-management behaviors, motivation and perceived autonomy support were assessed with a cross-sectional survey among parents of children with chronic conditions ( N  = 239). Statistical analysis involved descriptive statistics and univariate analysis of variance. The survey was followed by 18 in-depth interviews with parents. Thematic analysis was used to recognize relevant topics in the qualitative data. Results: In the survey most parents reported being active self-managers. Nevertheless, only one third persisted in self-management when under stress. Autonomous motivation was strongly associated with parental self-management. In the interviews, parents mentioned attuning with professionals and finding balance as important aspects of self-management. To facilitate self-management, professionals were expected to have expert knowledge, be engaged and empathic. Conclusion: From the perspective of parents, self-management should be viewed as a collaborative effort in which they are supported by professionals, rather than having to manage it "by themselves". Implications for rehabilitation: To facilitate self-management, parents expect professionals to have expert knowledge and additionally show interpersonal competences as openness, engagement and empathy. Motivating parents may facilitate their level of self-management regarding the care for their child with a chronic disorder. Good communication and collaboration with professionals appear to be key aspects of parental self-management. Parents expect pediatric rehabilitation teams to tune their services to the needs, desires and expectations of parents to support them in "self-managing" the care for their child.